1997
DOI: 10.1097/00004836-199701000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Immunodeficiency Virus Infection on Abdominal Tuberculosis in Western India

Abstract: We studied the seroprevalence of human immunodeficiency virus infection in patients with pulmonary tuberculosis and abdominal tuberculosis. We also assessed the clinical characteristics, risk factors, tuberculin status, site, and response to therapy of abdominal tuberculosis in human immunodeficiency virus (HIV)-seropositive and HIV-seronegative patients. Volunteer blood donors (n = 8,395), patients with pulmonary tuberculosis (n = 387), and patients with abdominal tuberculosis (n = 108) were screened for HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…There is a strong association with HIV co-infection. In abdominal TB, the HIV rate is almost double that of pulmonary TB (16.6% vs 6.9%) 15. HIV co-infection and disseminated TB are associated with increased morbidity and mortality from abdominal TB 16…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong association with HIV co-infection. In abdominal TB, the HIV rate is almost double that of pulmonary TB (16.6% vs 6.9%) 15. HIV co-infection and disseminated TB are associated with increased morbidity and mortality from abdominal TB 16…”
Section: Introductionmentioning
confidence: 99%
“…In a study from Mumbai, HIV seroprevalence was found in 16.6 per cent in patients with abdominal tuberculosis as compared to 1.4 percent in voluntary blood donors. 1 TB of the gastrointestinal tract is the sixth most frequent form of extra-pulmonary site, after lymphatic, genitourinary, bone and joint, miliary and meningeal tuberculosis. Abdominal tuberculosis can affect the gastro intestinal tract; peritoneum lymph nodes or the solid viscera including pancreas, spleen and occasionally pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…The recent increase in the prevalence rate of abdominal TB is believed to be a result of an increased prevalence of HIV infection in the world. 10 The demographic distribution of patients revealed that the disease occurred more commonly in male subjects in the age group of 40-60 years. The common clinical features included distention of abdomen (100%), pallor (83.33%) and pedal edema (50.00%).…”
Section: Discussionmentioning
confidence: 98%